127k views
4 votes
if log y=3(log 4 + log x), express y in terms of x. serious answers only please no files or nun of that.

1 Answer

3 votes

Answer:

The expression is
y = 64 + x^(3).

Explanation:

Let be
\log y = 3\cdot (\log 4 + \log x), the "log" component is refered to logarithms with base 10. By definition of logarithm and its properties, we derive an expression of
y in terms of
x:


\log y = 3\cdot (\log 4 + \log x)


10^(\log y) = 10^(3\cdot (\log 4 + \log x))


y = 10^(3\cdot \log 4)+10^(3\cdot \log x)


y = 10^{\log 4^(3)}+10^{\log x^(3)}


y = 64 + x^(3)

The expression is
y = 64 + x^(3).

User Ricardo Nolde
by
6.2k points